Selecting Blockchain Consensus Algorithms Integrations for IoT-based Enviroments - Morais, Anderson Melo de; Lins, Fernando Antonio Aires; Rosa, Nelson Souto (Anais do Latin-American Symposium on Dependable Computing (LADC); 2024: Anais do XIII Latin-American Symposium on Dependable Computing, 2024)
The Internet of Things (IoT) is transforming many sectors of society by enabling communication between smart devices, but it faces challenges in maintaining integrity in data recording. Traditional Blockchain technologies, such as those based on Proof of Work (PoW), are unsuitable for IoT due to their high demands on computational resources. There are proposals to use multiple consensus algorithms in the same blockchain solution to improve performance and integrity. However, choosing the best algorithms or combinations for each IoT scenario is an open challenge. This work presents a strategy to select consensus algorithms and optimize blockchain performance in IoT-based environments. The proposed strategy was simulated in a blockchain implemented atop a Directed Acyclic Graph (DAG) designed for IoT environments. This blockchain integrates multiple consensus algorithms - Proof of Authority (PoA), Proof of Stake (PoS), Proof of Work (PoW), Practical Byzantine Fault Tolerance (PBFT), and Raft - each selected for its performance and security advantages. A comparative evaluation of different combinations is presented. The results show the performance and adaptability of the proposed strategy in various scenarios.